2023
DOI: 10.3346/jkms.2023.38.e86
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Thickness and Its Interocular Asymmetry Between Parkinson’s Disease and Drug-Induced Parkinsonism

Abstract: Background Drug-induced parkinsonism (DIP) is common, but diagnosis is challenging. Although dopamine transporter imaging is useful, the cost and inconvenience are problematic, and an easily accessible screening technique is needed. We aimed to determine whether optical coherence tomography (OCT) findings could differentiate DIP from Parkinson’s disease (PD). Methods We investigated 97 de novo PD patients and 27 DIP patients using OCT and [ 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Patients with Parkinson's disease have a decreased average capillary retinal nerve fiber layer in every quadrant [104] They compared the two groups' peripapillary retinal nerve fiber layer and macular retinal thickness. There were no significant differences in peripapillary and macular retinal thickness values [106]. Suh et al's study is important because it showed that, in the early stages of drug-induced parkinsonism, there is no benefit in measuring these optic parameters to differ from early Parkinson's disease.…”
Section: Optical Coherence Tomographymentioning
confidence: 96%
“…Patients with Parkinson's disease have a decreased average capillary retinal nerve fiber layer in every quadrant [104] They compared the two groups' peripapillary retinal nerve fiber layer and macular retinal thickness. There were no significant differences in peripapillary and macular retinal thickness values [106]. Suh et al's study is important because it showed that, in the early stages of drug-induced parkinsonism, there is no benefit in measuring these optic parameters to differ from early Parkinson's disease.…”
Section: Optical Coherence Tomographymentioning
confidence: 96%